The folly of empire : what George W. Bush could learn from Theodore Roosevelt and Woodrow Wilson - Judis, John B. (Oxford University Press, 2006)
A century ago, the Theodore Roosevelt administration believed building an American empire was the only way the U.S. could ensure its role in the world, but came to see the occupation of the Philippines as America's "heel of Achilles." Woodrow Wilson, shocked by the failure of Americanintervention in Mexico and by the outbreak of World War I, came to see imperialism as the underlying cause of war and set about trying to create an international system to eliminate empires. But, the current Bush administration, despite the lessons of the past, has revived the older dreams ofAmerican empire--unde